Securitization, three streams model and biodiversity in the Global South: A case study of Western Ghats of India - Joseph, Justin; Sahu, Anjan Kumar; Vuori, Juha A. (Elsevier BV, 2025)
Biodiversity conservation is one of the most contentious issues in the Global South, particularly political
authority’s methods and objectives of managing conservation. This paper studies how political authority deals
with biodiversity conservation, and how different stakeholders respond to the conservation policy. In doing so,
the study employs the securitization framework and blends it with the Three Streams Model to find out the
political authority’s securitization process (which is state-driven and top-down). Additionally, Narrative Policy
Framework is employed to study the response of stakeholders (primarily local) to the securitization process.
Thus, the central objective of the paper is to examine the securitization of the Western Ghats, especially with
reference to Kerala, India. Based on the case study, the study finds that audiences in the Global South are capable of opposing securitization of biodiversity. In conjunction with functional actors, audience form assemblages and resist the deployment of extraordinary measures, thereby opposing securitization.